(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In modern society, the skills of working with information technology are becoming one of the most important factors in training future specialists in any field of activity. The use of a competence-based approach in the educational process contributes to the achievement of the main goal of higher education. One of the main goals of using information technologies in education is determined by the fact that they are most effectively implemented such didactic principles as science, accessibility, visibility, consciousness and activity of students. Information technologies open up wide opportunities for activating the formation of students research competence. The article deals with the place and effectiveness of using information technology for the formation of research competence of students.